Assessment of residential satisfaction with internationally funded housing projects in Gaza Strip, Palestine - Sabah, Faisal Yousef (Frontiers in Built Environment, 2023)
The internationally funded housing projects in Gaza Strip were initiated with the aim of providing secure and habitable housing for low-income families. Nevertheless, there remains a limited understanding of the level of satisfaction among residents dwelling in these housing units. This paper presents the outcomes of a survey conducted in Gaza Strip to assess residential satisfaction from international housing projects. This community-based cross-sectional descriptive study was conducted between October 2022 and March 2023. Data collection relied on a pre-tested structured questionnaire consisting of thirty-two items, and it targeted residents of Hamad City, an area within Gaza Strip where international housing projects are prevalent. The questionnaire encompassed inquiries into residents' socio-demographic characteristics, their satisfaction levels regarding the dwelling, services, and the residential environment, their contentment with the social milieu, as well as their preferences and aspirations regarding future housing. To ascertain predictor variables influencing overall satisfaction with public housing, stepwise regression analysis were conducted, exploring their relationships with this overarching satisfaction factor.The survey encompassed a total of 375 participants residing in Hamad City. The results revealed that the overall average satisfaction rates with respect to the dwelling, services, and the residential environment were 53.1%, 52.9%, and 49.0%, respectively, among the residents of Hamad City in the Gaza Strip. Furthermore, 49.9% (n=187) of the respondents expressed their inclination to recommend others to reside in Hamad City. Moreover, 40.0% (n=150) of participants were content with the floor building system in Hamad City, while 71.2% (n=267) concurred with the notion of allocating residential buildings based on residents' needs instead of a single predetermined site. Impressively, 78.4% (n=294) of the respondents encouraged donors to undertake projects akin to Hamad City. The regression analysis elucidated that overall satisfaction levels are predominantly influenced by the improvement in satisfaction pertaining to dwelling space sufficiency. Thus, a crucial recommendation emerging from this study is the consideration of augmenting dwelling space in forthcoming internationally funded housing projects, as this would significantly enhance overall residential satisfaction.